On a non-self adjoint eigenfunction expansion. (1984) - Naylor, D.
Abstract : This paper develops a formula of inversion for an integral transform similar to that associated with the names of Kontorovich and Lebedev. The kernel involves the Hankel functionH u ( 1 ) ( k r ), in whichr varies over a truncated infinite intervala ≤ r < ∞, wherea > 0 and the parameterk is complex. This kind of transform is useful in the investigation of functions that satisfy the Helmholtz equation and the condition of radiation.